Unsteady Magnetohydrodynamic Mixed Convective Flow of a Reactive Casson Fluid in a Vertical Channel Filled with a Porous Medium - Rundora, Lazarus (Diffusion and defect data. Solid state data. Pt. A, Defect and diffusion forum, 2021)
This article analyses the thermal decomposition in an unsteady MHD mixed convection flow of a reactive, electrically conducting Casson fluid within a vertical channel filled with a saturated porous medium and the influence of the temperature dependent properties on the flow. The fluid is assumed to be incompressible with the viscosity coefficient varying exponentially with temperature. The flow is subjected to an externally applied uniform magnetic field. The exothermic chemical kinetics inherent in the flow system give rise to heat dissipation. A technique based on a semi-discretization finite difference scheme and the shooting method is applied to solve the dimensionless governing equations. The effects of the temperature dependent viscosity, the magnetic field and other important parameters on the velocity and temperature profiles, the wall shear stress and the wall heat transfer rate are presented graphically and discussed quantitatively and qualitatively. The fluid flow model revealed flow characteristics that have profound ramifications including the increased heat transfer enhancement attributes of the reactive temperature dependent viscosity Casson fluid flow.